Palladium-catalyzed hydroaminocarbonylation of alkenes with amines promoted by weak acid. Issue 3 (20th January 2016) - Zhang, Guoying; Ji, Xiaolei; Yu, Hui; Yang, Lei; Jiao, Peng; Huang, Hanmin
Graphical abstract: Abstract: The weak acid has been identified as an efficient basicity-mask to overcome the basicity barrier imparted by aliphatic amines in the Pd-catalyzed hydroaminocarbonylation, which enables both aromatic and aliphatic amines to be applicable in the palladium-catalyzed hydroaminocarbonylation reaction. Notably, by using this protocol, the marketed herbicide of Propanil and drug of Fentanyl could be easily obtained in a one-pot manner.